2020
DOI: 10.1155/2020/4240380
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Elevated Alanine Aminotransferase by Diagnostic Criterion, Age, and Gender among Adolescents

Abstract: Background. Serum alanine aminotransferase (ALT) activity was measured not only to detect liver disease, but also to monitor overall health. The purpose of this study was to obtain the prevalence of elevated ALT levels among adolescents. Methods. In a school-based cross-sectional study, a representative sample was analyzed from 9 middle and high schools in Shenzhen, China, during 2017 to 2018. Elevated ALT was defined as diagnostic criterion I (>30 U/L for boys and >19 U/L for girls) and diagnostic crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The overall prevalence of elevated ALT and AST were 6.8% and 2.3% in our study. A school-based cross-sectional study in China reported a prevalence of 6.76% for ALT levels greater than 30 U/L for boys and 9 U/L for girls, compared with 2.43% at a cut-off level of greater than 40 U/L [ 20 ]. Asymptomatic elevation in ALT levels is common in primary care, and the prevalences of elevated ALT and AST in the United States were 8.9%, 4.9% respectively [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The overall prevalence of elevated ALT and AST were 6.8% and 2.3% in our study. A school-based cross-sectional study in China reported a prevalence of 6.76% for ALT levels greater than 30 U/L for boys and 9 U/L for girls, compared with 2.43% at a cut-off level of greater than 40 U/L [ 20 ]. Asymptomatic elevation in ALT levels is common in primary care, and the prevalences of elevated ALT and AST in the United States were 8.9%, 4.9% respectively [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, age and sex have been reported to be associated with differences in ALT activity, as levels tend to be higher in men than women. [9][10][11][12][13] This finding has led several liver societies to recommend separate sex-based upper limits of normal. Ethnic differences in ALT levels have also been observed.…”
Section: Aminotransferasesmentioning
confidence: 99%
“…Located in the Pearl River Delta region in southern China, Shenzhen is a major nancial centre in mainland China and the worldly largest manufacturing base, with a rapid economic development [20][21][22]. Based on the 2019 Shenzhen Baoan Statistical Yearbook (http://www.baoan.gov.cn/sjfb/tjsj/tjnj/), among the 10 district-level jurisdictions of Shenzhen, the Baoan District is accounted for the rst largest area with a total area of 396.61 km 2 ; accounting for a quarter of the total Shenzhen population, the total permanent resident population of Baoan was 3.34 million at the end of 2019, with a natural population growth rate of 21.92‰; the total gross domestic product was 385.36 billion CNY (ie, 59.63 billion USD) in 2019.…”
Section: Study Setting and Populationmentioning
confidence: 99%